PENGARUH MODEL PEMBELAJARAN POE (PREDICT-OBSERVE-EXPLAIN) TERHADAP HASIL BELAJAR IPA SISWA KELAS V SD - Novie Adeulliah; Liza Murniviyanti; Eni Heldayani (STKIP Subang, 2023)
ABSTRACT This study aims to determine the effect of the POE (Predict-Observe-Explain) learning model on science learning outcomes in grade V elementary school students. The formulation of the problem in this study is whether there is an influence on the use of the POE (Predict-Observe-Explain) learning model on science learning outcomes in grade V students of SD Negeri 17 Palembang for the 2023/2024 school year. This study used an experimental method with a True Experimental Design research design in the form of Posttest-Only Control Group. The population in this study is all grade V students of SD Negeri 17 Palembang for the 2023/2024 school year while the sample in this study is class V.A and V.B students, where class V.A students as a control class totaled 24 students and class V.B as an experimental class totaled 24 students. The research instrument used is a test question in the form of an essay question of 10 questions with the material of Animal Motion Organs. Based on data from posttest research results in both classes, it was found that the average value of the experimental class was greater than the control class, which was 80,946 > 63,437, besides that through hypothesis testing using the Mann Whitney U test obtained asymp. sig values. (2-tailed) in the posttest results of both classes is 0.003 with α = 0.05, so 0.003 < 0.05, it can be concluded that Ho was rejected and Ha was accepted, it can be concluded that there is an influence of the POE (Predict-Observe-Explain) learning model on science learning outcomes in grade V students of SD Negeri 17 Palembang. Keywords: POE Learning Model, Science Learning Outcomes